2019
DOI: 10.1080/10967494.2019.1659891
|View full text |Cite
|
Sign up to set email alerts
|

Citizens’ motivated reasoning about public performance: experimental findings from the US and Denmark

Abstract: Recent studies find motivated reasoning in citizens' processing of information about public performance. Using experiments in the US and Denmark, we examine effects on an accuracy-based task of two forms of motivated reasoning: partisan identity-based reasoning and reasoning from ideology-based governance preferences (favoring either the public or the private sector). The experiments incorporate a political prime, a health care needs prime (to reduce politicization), and a neutral, no-prime, condition. We find… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 30 publications
2
12
0
Order By: Relevance
“…Similar conclusions have been observed in public administration studies where scholars found that citizens tend to misinterpret performance information that is at odds with their prior beliefs (Baekgaard et al 2019; Baekgaard and Serritzlew 2015; James and Van Ryzin 2017). In a randomized survey experiment examining how Danish citizens interpret performance information about public and private providers of services, Baekgaard and Serritzlew (2015) observed that citizens tend to misinterpret evidence that contradicts their preferences for the public or private provision of services.…”
Section: Theoretical Framework and Development Of Hypothesessupporting
confidence: 79%
See 2 more Smart Citations
“…Similar conclusions have been observed in public administration studies where scholars found that citizens tend to misinterpret performance information that is at odds with their prior beliefs (Baekgaard et al 2019; Baekgaard and Serritzlew 2015; James and Van Ryzin 2017). In a randomized survey experiment examining how Danish citizens interpret performance information about public and private providers of services, Baekgaard and Serritzlew (2015) observed that citizens tend to misinterpret evidence that contradicts their preferences for the public or private provision of services.…”
Section: Theoretical Framework and Development Of Hypothesessupporting
confidence: 79%
“…They also assert that individuals who have strong prior political beliefs are prone to even more extreme behavior because they tend to uncritically accept consistent evidence while actively refuting inconsistent information (Lodge and Taber 2000;Taber, Cann, and Kucsova 2009;Taber and Lodge 2006). Similar conclusions have been observed in public administration studies where scholars found that citizens tend to misinterpret performance information that is at odds with their prior beliefs (Baekgaard et al 2019;Baekgaard and Serritzlew 2015;. In a randomized survey experiment examining how Danish citizens interpret performance information about public and private providers of services, Baekgaard and Serritzlew (2015) observed that citizens tend to misinterpret evidence that contradicts their preferences for the public or private provision of services.…”
Section: Local Delivery Preferences and Motivated Reasoningsupporting
confidence: 72%
See 1 more Smart Citation
“…Motivated goals include, for example, evaluative attitudes towards a group, actors, activities, objects and products and these goals have been studied by researchers specializing in social and cognitive psychology, economy and political science etc. (Baekgaard et al 2020 ; Donovan and Priester 2017 ; Epley and Gilovich 2016 ; James and Van Ryzin 2017 ; Kahan et al 2017 ; Redlawsk 2002 ). Redlawsk ( 2002 ) investigated political decision making in an experimental setting.…”
Section: Introductionmentioning
confidence: 99%
“…We will also apply the Cultural Cognitive Worldview Scales, CCWS (Kahan et al 2011 ) which aims at describing individualism versus egalitarianism. We included this scale because individualism is correlated with attitudes towards private and public health care as shown by, for example, Baekgaard and colleagues (Baekgaard, et al 2020 ). Cognitive reflection test, CRT, items were also included in the study because mathematical/logical ability has been shown to correlate negatively with motivational bias (Lind et al 2018 ).…”
Section: Introductionmentioning
confidence: 99%